Visual Merchandising Strategy Analysis - Sari , Wahyu Tri Retno; Surianto, Moh. Agung (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Visual merchandising is an essential component of modern retail, as it shapes consumer perceptions and influences the shopping experience through attractive, informative, and well-structured visual elements. Its effectiveness plays a key role in building store image, improving navigation, and encouraging purchasing behavior. Based on this importance, the present study aims to analyze the implementation of visual merchandising strategies at Alfamart Bungah, Gresik, focusing on three main elements: window displays, floor merchandising, and promotional signage. This research employs a qualitative case study approach through in-depth interviews with store managers, employees, and consumers, supported by direct observation and documentation. The findings indicate that although Alfamart Bungah follows standard corporate guidelines, the visual merchandising practices are not yet effective in capturing consumer attention or facilitating navigation. The window displays appear simple and less attractive, the floor merchandising area is crowded and lacks category boards, and promotional signage is less communicative due to suboptimal placement and irregular updates. Consumers perceive the store as neat and clean but expect more engaging and informative visual arrangements. This study concludes that improvements in visual design, layout optimization, and signage quality are needed to enhance store image and strengthen the overall customer shopping experience.